Hubungan Kekerabatan Lima Spesies Dari Family Poaceae Berdasarkan Karakter Morfologi - Zaniati, Putri Mona; Alami, Zulfa Wasiatul; Nalirsa, Salwa; Rizqullah, Argya Rifqy; Sinaga, Rio Ferdinand; Febrianti, Arikah (PendIPA Journal of Science Education, 2025)
Indonesia is known as one of the countries with the highest biodiversity in the world, including in the Poaceae family or grasses that have important ecological and economic values. This study aimed to determine the kinship of five species from the Poaceae family based on morphological characters. The species observed include Cenchrus longispinus, Paspalum plicatum, Imperata cylindrica, Setaria parviflora, and Eleusine indica. The study was conducted quantitatively with a descriptive approach, through direct observation of morphological characters such as roots, stems, leaves, flowers, fruits, and seeds. Data were analyzed using a similarity index and visualized in the form of a dendogram. The results show that the five species have many morphological similarities, especially in root type, stem shape, growth direction, and flower type. The species with the closest kinship are Eleusine indica with Paspalum plicatum, and Cenchrus longispinus with Setaria parviflora. Meanwhile, the most distant relationship was found between Imperata cylindrica with Cenchrus longispinus and Setaria parviflora. PCA analysis was also used to identify the most influential morphological characters in distinguishing species. The results of this study provide an initial overview of the taxonomic relationships in the Poaceae family and the importance of morphological characters in plant systematics studies.